Gathering places : Aboriginal and fur trade histories - Peers, Laura L. (Laura Lynn); Podruchny, Carolyn (UBC Press, 2010)
Gathering Places presents some of the most innovative and interdisciplinary approaches to metis, fur trade, and First Nations history being practised today. Whether they are discussing dietary practices on the Plateau, trees as cultural and geographical markers in the trade, the meanings of totemic signatures, issues of representation in public history, or the writings of Aboriginal anthropologists and historians, the authors link archival, archaeological, material, oral, and ethnographic evidence to offer novel explorations that extend beyond earlier scholarship centred on the archive. They draw on Aboriginal perspectives, material forms of evidence, and personal approaches to history to illuminate cross-cultural encounters and challenge older approaches to the past."--pub. desc.